The Influence of Good Corporate Governance (GCG) toward Financial Performance - Bayunitri, Bunga Indah; Sihaloho, Theresia Veni; Sukma, Irene; Lasniroha, Tetty (Kompartemen : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine how good corporate governance has an affects to the financial performance at PT. Perusahaan Listrik Negara (PLN) for the period 2014-2018. The factors tested in this research were good corporate governance as the independent variable, while the company's financial performance was the dependent variable. The research method used in this research is explanatory method. The data analysis used in this study was a simple linear regression analysis at a significance level of 5%. Hypothesis test results indicate that good corporate governance and corporate financial performance have a positive effect by contributing 32.9% in influencing financial performance.